2020
DOI: 10.36294/jurti.v4i2.2103
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Data Mining untuk Manajemen Bantuan Sosial Menggunakan Algoritma K-Means

Abstract: Abstract- Every sub-district in North Sumatra Province can administer aid funds, one of which can provide priority community assistance to low-income families who are part of the Hope Family Program (PKH). The level of data accuracy must support the regional government's good intentions in alleviating poverty through the family hope program (PKH) for low-income families. There are complexities in processing data so far, that is, determining the poor population who are the top priority for receiving assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…With the conclusion, the results of the entire thesis will be known and it is hoped that with suggestions there will be improvements and benefits for others. [3], [4], [8]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the conclusion, the results of the entire thesis will be known and it is hoped that with suggestions there will be improvements and benefits for others. [3], [4], [8]…”
Section: Discussionmentioning
confidence: 99%
“…[1], [2], [5] This research is reinforced by previous studies related to the title, the first research conducted by (Achmad Fikri Sallaby and Eko Suryana) with the title "Application of Data Mining to Determine the Number of Registered Job Seekers Based on Age and Education Using K-Means Clustering (Case Study in Department of Manpower and Transmigration Bengkulu Province)" concluded that the results of processing with Data Mining facilitate grouping the number of registered job seekers based on age and education, making it easier for job seekers to obtain information. [1], [4], [7]…”
mentioning
confidence: 99%
“…With the conclusion, the results of the entire thesis will be known and it is hoped that with suggestions there will be improvements and benefits for others. [7], [10], [11]…”
Section: Discussionmentioning
confidence: 99%
“…The research methodology contains knowledge that examines the methods used in research. [4], [9]- [11] Based on the research methodology used in this study, a research framework activity flow can be made as shown in Figure below:…”
Section: Methodsmentioning
confidence: 99%